2000
DOI: 10.1103/physrevlett.85.282
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Funneling in Extended Dendrimers with Nonlinear and Random Potentials

Abstract: The mean first passage time (MFPT) for photoexcitations diffusion in a funneling potential of artificial tree-like light-harvesting antennae (phenylacetylene dendrimers with generation-dependent segment lengths) is computed. Effects of the non-linearity of the realistic funneling potential and slow random solvent fluctuations considerably slow down the center-bound diffusion beyond a temperature-dependent optimal size. Diffusion on a disordered Cayley tree with a linear potential is investigated analytically. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 26 publications
1
43
0
Order By: Relevance
“…8 These applications, and the fundamental physics and chemistry behind novel dendritic macromolecular architectures, have motivated the investigation of the mechanisms involved in the energy transfer processes in novel organic dendrimers. [7][8][9][10][11][12] There has been a widespread interest in the research to mimic the natural photosynthesis process. Natural photosynthetic systems have been investigated for their light harvesting properties by a variety of methods.…”
Section: Introductionmentioning
confidence: 99%
“…8 These applications, and the fundamental physics and chemistry behind novel dendritic macromolecular architectures, have motivated the investigation of the mechanisms involved in the energy transfer processes in novel organic dendrimers. [7][8][9][10][11][12] There has been a widespread interest in the research to mimic the natural photosynthesis process. Natural photosynthetic systems have been investigated for their light harvesting properties by a variety of methods.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative way to obtain this increased density of wrong turns is to have disorder, both dynamic and static, in the model. Mukamel and co-workers have shown that energetic disorder can lead to the loss of efficient transfer in funnel-type dendrimers, 66,67 and similar effects could be operative in our molecules. As the size of the dendrimer increases, the probability of encountering a low-energy site before trapping increases as well, leading to a steeper decline in trapping efficiency than would be expected for a model where all the sites are identical.…”
Section: S(λt) ) a M (T)s M (λ) + A E (T)s E (λ)mentioning
confidence: 96%
“…Heijs et al [27] studied dendrimers via a hopping model using a Id asymmetric random walk where they incorporated non-radiative decay and a linear energy bias. Using Laplace transforms of the relevant equations, they analyzed the problem in the Laplace domain and found the trapping time distribution, and its first and second moments for large N. The general solution in the Laplace domain is unable to be transformed back to the time domain, but they were able to obtain expressions for particular cases.…”
Section: Theoreticalmentioning
confidence: 99%
“…Of particular interest in this study is their use as light-harvesting complexes and artificial antennae in the context of energy storage and transfer [1,2,3,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37].…”
Section: Introductionmentioning
confidence: 99%